Facile Postsynthesis of N-Doped TiO2-SBA-15 and Its Photocatalytic Activity - Thu Phuong Tran Thi; Duc Trieu Nguyen; Tuan Quang Duong; Huy Hoang Luc; Vien Vo (Advances in Materials Science and Engineering)
N-doped TiO2-SBA-15 (denoted as N-TiO2-SBA-15) material has been successfully synthesized by a two-step procedure. Firstly, TiO2-SBA-15 was prepared by impregnating tetraisopropyl orthotitanate on SBA-15 and followed by calcination at 550°C. In the second step, TiO2-SBA-15 was modified by doping nitrogen with the assistance of urea. The resulting material, N-TiO2-SBA-15, was characterized by XRD, TEM, SEM, N2 adsorption/desorption at 77 K, DR UV-Vis, and XPS. The results showed that N-TiO2-SBA-15 material maintains its ordered hexagonal mesostructure and exhibits the absorption of visible region. The photocatalytic activity of N-TiO2-SBA-15 sample was evaluated by the photodegradation of methylene blue under visible light.